Extreme point South Triangle recreational facility - Reyes, David Joshua D.; Meonada, Jose Mari E. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The proposed development is located in Barangay South Triangle, home of the so-called "entertainment and night-life districts" of Quezon City : Tomas Morato Avenue and Timog Avenue. The developing area has started to transition from residential district to major commercial district with the rise of Quezon City Central Business District. Aside from the communal spaces, it will be the home to the needy and the rising trends in the world of recreational activities, may it be in sports, extreme sports or in health and fitness. The design would therefore not be limited to physical means but also with emerging technological advancements. Furthermore with the said concerns, it will cater the spaces that meet both the recreational and commercial aspects of the design. The proposed facility will also be the home of a community with its residential tower to further aid in the generation of income. Altogether it will be a mixed-use high rise development for extreme sports and recreational facilities that will cater not just for kids and youth but also to families.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Recreational facilities -- South Triangle